(untitled) (Revista de Ciências Agroveterinárias, 2021)
Alternative agricultural activities, such as the strawberry crop, have attracted the interest of some farmers in western Santa Catarina (southern Brazil). The objective of this work was to carry out a diagnosis of the commercial production of strawberries of this region in the 2020 harvest cycle, enabling the planning of technical assistance actions in the cultivation and development of the production chain. Data were collected through specific questionnaires applied to Epagri (Agricultural Research and Extension Company of the State of Santa Catarina) rural extensionists responsible for the municipalities belonging to Technical Management Unit 1 (UGT 1 - Western Santa Catarina), which encompasses 36 municipalities. Data were systematized according to the following parameters: number of producers and plants per municipality; number of plants per cultivar; percentage of “first cycle” or “two or more cycles” plants; number and percentage of farmers that: i) adopted the same origin of the seedlings used; ii) received or not some technical assistance; iii) have a proper production system; iv) adopted a proper cultivation system; v) have a production traceability; and vi) adopted commercial value and form of commercialization. Results show that the Western administrative region of the Santa Catarina state has 68 strawberry producers, and they are present in 67% of the municipalities and cultivating 358.565 plants. The cultivars Albion and San Andreas are being the most one used. Most cultivated areas are conventional (70,6%), and use the semi-hydroponic system in benches and high tunnels (60,3%). Sales in natura and directly to the consumer are carried out by most growers, with an average sales value of R 19,81/kg of fruit (3.70 USD). These outcomes must be taken into account when planning the development of the production chain in the selected region.